Effort estimation of open source Android projects via transaction analysis. Issue 1 (21st February 2020) - Qi, Kan; Boehm, Barry
Abstract: Transactions have been used in many software sizing methods to measure software functional size and provide a basis for effort estimation. To further investigate the effects that transactions have on software functional size and more accurately estimate project effort using the transactional information, in this paper, we propose a method to identify transactions, as well as their complexity attributes that are influential to software functional size, directly from the source code of Android projects using static and dynamic analyses. The identified transactions are classified into different complexity levels and applied with different weights based on their evaluated complexity levels to distinguish their effects on software functional size. A size metric called sum of weighted transactions (SWT) is proposed to measure software functional size. We calibrate an effort estimation model using SWT based on a data set of 34 open source Android projects, and show the effectiveness of using SWT as a software functional size measure to estimate project effort.